Solving equations

Apphysics

New member
Joined
Aug 3, 2014
Messages
7
ax + by = c
y = dx + e

solve for x and y. I am confused if it can be done. How can you solve for y when it is given. Thank you.
 
ax + by = c .......................(1)
y = dx + e .......................... (2)

solve for x and y. I am confused if it can be done. How can you solve for y when it is given. Thank you.

It is given in terms of 'x' - you need to eliminate 'x' and solve it in terms of a, b, c, d & e.

To that first solve for 'x' -

ax + by = c ............substitute 'y' here using eqn. # 2

ax + b*(dx + e) = c

Then use that 'expression" of x into (2) to solve for 'y' it in terms of a, b, c, d & e (without x).
 
It is given in terms of 'x' - you need to eliminate 'x' and solve it in terms of a, b, c, d & e.

To that first solve for 'x' -

ax + by = c ............substitute 'y' here using eqn. # 2

ax + b*(dx + e) = c

Then use that 'expression" of x into (2) to solve for 'y' it in terms of a, b, c, d & e (without x).

Thank You, I really appreciate it.
 
Top